The effectiveness of item parceling to increase the model fit: A case study of PAPs - Hapsari, Anindita Dwi; Widhiarso, Wahyu (Jurnal Penelitian dan Evaluasi Pendidikan, 2023)
The impact of item parceling to improve model fit indexes in confirmatory factor analysis has been on debate amongst psychometricians. In this study, the effectiveness of item parceling was examined using Tes Potensi Akademik Pascasarjana (PAPS) or Postgraduate Academic Potential Test in Universitas Gadjah Mada. Item parceling approach, second-order approach, and item-based approach of confirmatory factor analysis (CFA) were used for examination. Data were collected from a sample of 1374 postgraduate candidates in 2017. The result found that model fit indices such as the chi-squared test, comparative fit index, Tucker-Lewis index, and standardized root mean square residual were improved in the item parceling approach when compared to item based approach. Interestingly, the root mean square error of approximation were deteriorating in the item parceling approach. The finding of this study suggested that model dimensionality and sample size should be carefully considered when using the item parceling approach.